Biography and social exclusion in Europe : experiences and life journeys / edited by Prue Chamberlayne, Michael Rustin and Tom Wengraf with Roswitha Breckner [and others]. - Chamberlayne, Prue; Wengraf, Tom; Rustin, Michael (Policy Press, 2002)
Throughout Europe, standardised approaches to social policy and practice are being radically questioned and modified. Beginning from the narrative detail of individual lives, this book re-thinks welfare predicaments, emphasising gender, generation, ethnic and class implications of economic and social deregulation.